Sunday

April 20, 2014

April 20, 2014

Posted by **Jaz** on Saturday, November 21, 2009 at 8:42pm.

- Dividing Rational Expressions -
**Reiny**, Saturday, November 21, 2009 at 9:00pmyes!

We can factor both the sum and the difference of cubes

A^3 + b^3 = (A+B)(A^2 - AB + B^2) and

A^3 - b^3 = (A-B)(A^2 + AB + B^2)

that is where those factors came from.

Most of the stuff canceled and you should have had x^2 - 2x + 4 as the answer.

**Related Questions**

Rational Expression - (x+1/2x-1 - x-1/2x+1) * (2x-1/x - 2x-1/x^2) (x+1/2x-1 - x-...

Algebra - I multiplyed x^2-2x+2 times x^2+2x+2. The book suggested the order ...

TO KIM - can you help me with this |2x - 3|^2 - 6|2x - 3| + 5=0 I know you are ...

Math33333 - Please help me! Problem: x+2 x-3 _________ - _________ 2x^2+5x+2 2x^...

math - how many times does the graph of y= 2x squared -2x+3 intersect the x-axis...

Algebra - Need help with this problem, 2x+y=6 solve for y 2x+y=6 subtract 2x ...

math/algebra - divide: x^2 + 2x -15/4x^2 divided by x^2-25/2x-10 answer choices ...

Math - Null factor law and factoriising: 2x^2+7x=0 X(2x+7)=0 X=0 or 2x+7=0. ( ...

algebra - Division Polynomials 2x square + 4 /2x 2x^2 + 4/(2x) = 2 (x^2 + 1/x) ...

algebra - I need to know if I am doing this problem right when sustitution ...